Implementasi Sleepiness EWS Pada TRC BPBD Jember Sebagai Usaha Pengurangan Risiko Kecelakaan Kerja - Bakhtiyar Hadi Prakoso; Gandu Eko Julianto Suyoso; Veronika Vestine; Sugeng Hartanto; Angga Rahagiyanto (Journal of Community Development, 2024)
The Quick Response Team (TRC) of BPBD Jember plays an important role in disaster management. Among their emergency response activities are the mobilization of personnel for victim assistance and the distribution of aid to disaster victims. The nature of TRC's work demands both physical and mental effort. This poses a risk of work fatigue, one manifestation of which is microsleep, which can lead to traffic accidents as experienced by the TRC in 2019. The objective of this community service activity is to implement artificial intelligence that can monitor driver activity to reduce the risk of traffic accidents. The method of this service activity involves the installation of a sleepiness early warning system (EWS) in TRC BPBD Jember vehicles. The device is mounted on the dashboard, facing the driver, and powered by a 12-volt car battery. Based on interviews, the implementation of the sleepiness EWS in the operational vehicles of TRC BPBD Jember has been able to enhance driving safety by providing warnings to drivers when they begin to lose concentration, whether due to fatigue or distractions. Although there were challenges in implementing the device, such as slow response time and limited detection range, the community service team overcame these issues by recalibrating the device's response time and selecting drivers with similar anthropometric measurements to avoid the need for frequent adjustments when changing drivers.